Bodily feelings and aesthetic experience of art - Nummenmaa Lauri; Hari Riitta (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
Humans all around the world are drawn to creating and consuming art due to its capability to evoke emotions, but the mechanisms underlying art-evoked feelings remain poorly characterised. Here we show how embodiement contributes to emotions evoked by a large database of visual art pieces (n = 336). In four experiments, we mapped the subjective feeling space of art-evoked emotions (n = 244), quantified "bodily fingerprints" of these emotions (n = 615), and recorded the subjects' interest annotations (n = 306) and eye movements (n = 21) while viewing the art. We show that art evokes a wide spectrum of feelings, and that the bodily fingerprints triggered by art are central to these feelings, especially in artworks where human figures are salient. Altogether these results support the model that bodily sensations are central to the aesthetic experience.